A rare case of plantar epithelioma cuniculatum arising from a wart - Rahul Ray; Aditi Bhagat; Biju Vasudevan; Jandhyala Sridhar; Renu Madan; Manjusha Ray (Wolters Kluwer Medknow Publications, 2015)
A 68-year-old man, a known case of hypertension, coronary artery disease and old cardiovascular accident with right-sided hemiplegia, came with the chief complaints of a large cauliflower like growth with pus discharge on the left heel since 15 years. The patient had sustained a penetrating injury by a thorn on the left heel region few days before the lesion appeared. Dermatological examination revealed a single verrucous lesion measuring 7 × 7 cm on the left heel region associated with discharge of foul smelling cheesy material. There was also a enlarged right inguinal lymph node which was non-tender, firm, measuring 2 cm in diameter with normal overlying skin. X-ray left ankle was done which showed some soft tissue swelling. A skin biopsy showed hyperkeratosis, acanthosis and parakeratosis. Elongated rete ridges with keratinocyte hyperplasia, forming a large mass pressing on the underlying dermis were seen. There was formation of multiple large keratin filled invaginations and crypts. No atypical cells were seen. Based on history, clinical examination and investigations, a diagnosis of epithelium cuniculatum type of verrucous squamous cell carcinoma was made. A wide excision with a flap cover was performed in consultation with the oncosurgeon and the excision sample was sent for histopathological re-examination, which confirmed the diagnosis of epithelioma cuniculatum.